Mediating effect analysis of postprandial triglyceride on Omega-3 and nonalcoholic fatty liver disease in individuals with normal fasting lipid levels - Li, Luxuan; Tang, Yale; Hou, Yilin; Wang, Xiaoyu; Liu, Dandan; Tian, Peipei; Song, Guangyao (Frontiers in Physiology, 2026)
BackgroundThe association between Omega-3 (ω-3)and non-alcoholic fatty liver disease (NAFLD) in individuals with normal fasting lipid levels subjects is unclear. In addition, few studies have explored whether postprandial triglyceride levels (PTG) mediates the association between ω-3 and NAFLD. We aimed to analyze the mediating effect of PTG on ω-3 and NAFLD.MethodsIn March 2024, volunteers were recruited from the Hebei Provincial People’s Hospital. In total, 108 volunteers met the inclusion criteria. The basic information and biochemical parameters, as well as ω-3 and PTG were collected. NAFLD was diagnosed according to abdominal ultrasonography. The clinical characteristics of the participants was analyzed by quartiles of ω-3 (O1-O4 quartiles) and PTG (P1-P4 quartiles), respectively. Pearson correlation analysis was performed to investigate the correlation between ω-3 and PTG. Multivariate logistic regression analysis was applied to analyze the effect of ω-3 and PTG on NAFLD. Bootstrap was conducted to explore whether PTG mediated the association between ω-3 and NAFLD.ResultsPearson correlation analysis indicated that ω-3 was negatively associated with PTG. Multivariate logistic regression analysis indicated that compared to the low ω-3 group, the risk of NAFLD significantly decreased in high ω-3 group [OR = 0.024 (0.006 ∼ 0.104)]. Mediating effect analysis showed that ω-3 significantly directly influenced NAFLD prevalence [β = −0.077, 95%CI (−0.128, −0.026)], and PTG partly mediated the indirect effect of the ω-3 on NAFLD prevalence [β = −0.084, 95%CI (−0.130, −0.037)], and the mediating effect accounted for 52.17% of the total effects.ConclusionIn this cross-sectional analysis, both ω-3 and PTG were predictors of NAFLD, and PTG partly statistically mediated the indirect effect of the ω-3 on NAFLD prevalence.